Hablumminannas: Nilai-Nilai Keislaman dan Praktiknya Dalam Pergaulan Antar Ikhwan dan Akhwat Pada Organisasi Forum Lingkar Pena Makassar - Andi Batara Al Isra (ETNOSIA : Jurnal Etnografi Indonesia, 2016)
Forum Lingkar Pena (FLP) Makassar is one of the organizations with Islam as its ideology. Its members come from various organization, and therefore this has influenced their perception on the practice of Islamic values in the context of hablumminannas. This article deals with how Islamic values are applied in the every day life of members of FLP and how members of FLP manage to deal with this. It was found that their understanding in the application of Islamic values regarding human relations vary, particularly in regard to the interaction between men (ikhwan) and women (akhwat). The variety of understanding is debated and influences the relation between members of FLP. Those whose background are from WahdahIslamiyahand Hizbut Tahrir Indonesia tend to be rigidly reacted to these differences, while others are more moderate. Some resists and follow the majority and still try to make a difference; others are disappointed, but keep themselves in FLP to respect others’ perception without being active in FLP activities; the rests are resisted and left FLP as a result. However, such differences are common as long as they have the basis of their responsesince FLP promotes unity and harmony among its members. Despite the fact, they basically have the same understanding on the basic principle on the aspects that related to hablumminannas, they are different in the way to practice them, such as, among others, shaking hand, being alone between ikhwan and akhwat, riding between ikhwanandakhwat, using hijab to separate between ikhwan and akhwat. It was argued in this article that their understanding in the application of Islamic values in the interaction between ikhwan and akhwat is greatly influenced by their background and the circumstances.